The Edinburgh companion to Globalgothic - Duncan, Rebecca, Dr (Edinburgh : Edinburgh University Press, 2023)
"The Edinburgh Companion to Globalgothic is the most substantial exploration to date of gothic fiction in the international context. Examining texts from across six continents, the volume considers how gothic imagines, colludes with or interrogates relationships and phenomena that are planetary in scale. Accordingly, chapters address gothic engagements with - among others - resource imperialism, (ongoing) colonial history, diasporic identity, buckling economic unions, the rise of the internet, enthnonationalism, and entangled systems of gendered, racialised and ecocidal power. In this way, the collection moves decisively beyond the framework of globalisation to identify a range of new globalgothic approaches and modes, overall demonstrating that gothic is a key - though sometimes complicit - register for negotiating the challenges and histories of our uneven global present." --
Acknowledgements -- Introduction: Globalgothic beyond globalisation / Rebecca Duncan -- Part I. Approaches -- Decolonial gothic / Sheri-Marie Harrison -- The world-system of global gothic, horror and weird / Stephen Shapiro -- Economy of shadows, work of death: necropolitics, slavery, zombi/e / Fred Botting -- Gothic and the Black diaspora / Maisha Wester -- Engendering Globalgothic: the 'Hideous Progeny' of Mary Shelley's Frankenstein / Monica Germanà -- Queering Globalgothic ecologies / Gregory Luke Chwala -- Anthropocene gothic, capitalocene gothic: the politics of ecohorror / Rebecca Duncan -- Extractive gothic / Sharae Deckard -- Part II. Issues -- US imperial gothic / Kevin Corstorphine -- Globalgothic and War / Agnieszka Soltysik Monnet -- Terrorist gothic / Steffen Hantke -- Neoliberal Globalgothic: the Trump White House, the Alt-right and the long-heralded death of the dream / Linnie Blake -- New weird technologies: subverting Neoliberal globalisation through hybridity / Elsa Bouet -- Uncanny Globalgothic ecologies: animate intimacies / Chloé Germaine -- Pandemics and Globalgothic / Johan Höglund -- Medical Globalgothic: organ harvesting and the Red Market / Laura R. Kremmel -- Part III. Modes -- Globalgothic translations and migrations: from Britain to Brazil / Sandra Guardini Vasconcelos -- Gothic literary travel and global tourism / Lucie Armitt -- Gothic and global travel writing / Sofia Aatkar -- Folk horror and the Globalgothic / Timothy Jones -- Brexit gothic / Roger Luckhurst -- Online gothic / Xavier Aldana Reyes -- Part IV. Regions and Geographies -- Gothic and the global south / Rebekah Cumpsty -- Migration and the gothic: border gothic / Enrique Ajuria Ibarra -- Globalgothic Americas: consuming and consumed bodies in twenty-first-century narratives / Inés Ordiz and Sandra M. Casanova-Vizcaíno -- Tropical gothic: plantation ecology, commodity frontiers and the aesthetics of excess / Esthie Hugo -- Asian gothic: Asian folklore and Globalgothic / Katarzyna Ancuta -- Desert Globalgothic / Rune Graulund -- Queer gothic narratives of Palestine in Alon Hilu's The house of Rajani and Ayman Sikseck's Tishrin / Karen Grumberg -- Nordic gothic / Yvonne Leffler -- 'In Brussels no one can hear you scream': EU gothic / Barry Murnane -- Coda -- Planetary gothic: an invitation / Rebecca Duncan -- Notes on Contributors -- Index.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (DeGruyter, viewed on January 12, 2024).
eBooks on EBSCOhost
Keywords: Gothic fiction (Literary genre) -- History and criticism; LITERARY CRITICISM / Gothic & Romance; Gothic fiction (Literary genre); Criticism, interpretation, etc